Interlaminar Cervical Epidural Non-Particulate Steroid Injection for Acute Cervical Radicular Pain: A Case Study of Clinical Effectiveness - Nur Azza, Kamala Kan; Susianti, Noor Alia; Mahmud, Mahmud; Nathania, Caroline Evanthe (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2021)
Background: Cervical radicular pain is pain that arises in the upper extremities caused by ectopic activities of afferent nociceptive or radix medulla spinalis. The pain intervention which can be done is interlaminar cervical epidural steroid injection (ICESI), transforaminal epidural steroid injection (TFSI), thermal radio frequency (TRF), pulse radio frequency (PRF), spinal cord stimulation (SCS), or surgery. Each modalities have different benefits and side effects. The success of ICESI is still debatable. This case report aimed to evaluate the success of ICESI for cervical radicular pain.Case: A woman, 71 years old, suffered from neck pain with radicular pain along the arm, until the palm, thumbs, and index finger on both right and left sides. The patient reported persistent pain predominantly in the palms, with an intensity of 7 out of 10 on the numeric rating scale (NRS). She felt the pain for 2 months, and it wasn’t relieved with pharmacotherapy and physiotherapy. The cervical magnetic resonance imaging (MRI) showed entrapment at the radix C6. The patient was advised to undergo an operative procedure, but the patient refused it and was offered an ICESI.Discussion: The ICESI approach has been proven to be effective in managing acute cervical radicular pain. By delivering corticosteroids into the epidural space, ICESI reduces inflammation around the affected nerve roots, leading to significant pain relief and improved functional outcomes, and allows for a broader spread of medication across multiple levels.Conclusion: ICESI is effective for cervical radicular pain.